Improving Trust and Accountability in AI Systems through Technological Era Advancement for Decision Support in Indonesian Manufacturing Companies - Eri Mardiani; Loso Judijanto; Arief Yanto Rukmana (West Science Interdisciplinary Studies, 2023)
This study explores how technological developments in Artificial Intelligence (AI) decision support systems within Indonesian manufacturing organizations interact with the intricate dynamics of trust, accountability, and technology. The study employed a cross-sectional quantitative research approach to gather responses from a representative sample of professionals spanning different organizational levels, age groups, and functions. The results show that there is a high degree of trust in AI systems, which is largely impacted by dependability and transparency. Strong perceived accountability frameworks encourage prudent decision-making. Technological developments have a big impact on trust and responsibility, especially in Explainable AI and bias prevention. A nuanced interpretation is ensured by the study's demographic analysis, which provides practitioners and policymakers with practical insights to support ethical AI integration in Indonesia's industrial sector.